Estudo farmacologico do óleo essencial do Croton nepetaefolius Baill sobre os musculos lisos traqueal e vascular e sobre as propriedades eletrofisiologicas de neuronios fasicos de ganglio celiaco - Magalhães, Pedro Jorge Caldas (2002)
Croton nepetaefolius is an aromatic bush found in brazilian Northeast region, called “marmeleiro sabiá”, and it is used in folk medicine as an antispasmodic and carminative agent. Its essential oil is comprised of 1,8-cineole, methyl-eugenol, xanthoxylin, terpineol and others constituents. Recent studies showed some pharmacological activities of the essential oil of Croton nepetaefolius (EOCN) as an intestinal antispasmodic, hypotensive, anti-inflammatory and analgesic agent. Our aim in this work was to evaluate the effects of EOCN on airway and vascular smooth muscle and also on autonomic neurons. We used in vitro models of rat and guinea-pig isolated vessels and guinea-pig tracheal rings for isometric recording of the smooth muscle contractions. Guinea-pig celiac ganglion, was used for intracellular microelectrode recording of electricophysiological signals. Moreover, mean arterial pressure, cardiovascular, respiratory and hematologic parameters were measured in vivo in rats. EOCN (0,1 – 1000 microgram/ml) relaxed basal and K+-increased guinea-pig tracheal tonus (EC50 = 4 and 63 microgram/ml, respectively), in a concentratation-dependent manner. In ovalbumin-sensitized guinea-pig tissues, EOCN inhibited the antigen-induced contraction. EOCN (100 - 400 microgram/ml) blocked the histamine- and PGF2alpha -induced contractions. The contractions induced by histamine, carbacol and KCl were inhibited by EOCN with IC50s between 100-130 microgram/ml. In rat and guinea-pig aortic rings, EOCN relaxed the 60 mM K+-induced contractions (IC50 = 32 and 200 microgram/ml, respectively). Only in rat tissues, this EOCN-induced relaxation was partially inhibited by both L-NAME (100 microgram M) or endothelium lack. In guinea-pig aortic rings, EOCN inhibited the Ca2+-independent phorbol esther- and hyperosmotic K+- induced contractions. EOCN, preferably, diminished the mean arterial pressure and inhibited the aortic rings phenylephrine-induced contractions in DOCA-salt treated rats rather than uninephrectomized rats. Both EOCN, methyl-eugenol and terpineol increased the flow through rat mesenteric bed. This effect was partially blocked by L-NAME (50 microgram M). EOCN did not produce hyperpolarization of the transmembrane potential. In celiac ganglion phasic neurons, EOCN signicantly inhibited the histamine-induced increase of the neuronal excitability. In conclusion, EOCN is an airway smooth muscle relaxant, hypotensor and vasorelaxant agent, and it is a blocker of the stimulant histamine activity on autonomic neurons. Its effects are, probably, mediated by an intracellular action or protein C kinase modulation.